Professional and interprofessional identities: a scoping review - Tong, R.; Brewer, Margo; Flavell, Helen; Roberts, Lynne (TAYLOR & FRANCIS INC, 2020)
Identity development within the interprofessional field is an emerging area of research. This scoping review aims to establish how professional and interprofessional identities are defined, conceptualized, theorized and measured within the interprofessional literature. Six databases were systematically searched for papers focusing on professional and/or interprofessional identities in interprofessional healthcare and education using a scoping review methodology. A total of 84 papers were included. Most papers discussed professional identity only; the minority discussed both identities. There were three key findings. First, no universal definition of interprofessional identity exists. Second, there is no shared understanding of interprofessional identity and its relationship with professional identity. Third, poor alignment between definitions, conceptualizations, theories and measures of interprofessional identity exists. The absence of a psychometrically robust instrument that specifically measures interprofessional identity and the short-term focus of current interprofessional identity research further limits understanding. Research that critically examines professional and interprofessional identity development should be underpinned by clear definitions, concepts, theories and measures of both identities. High-quality research will allow greater understanding of interprofessional identity development and its impact on interprofessional practice.